2007
DOI: 10.1099/ijs.0.65340-0
|View full text |Cite
|
Sign up to set email alerts
|

Reclassification of Aquaspirillum itersonii and Aquaspirillum peregrinum as Novispirillum itersonii gen. nov., comb. nov. and Insolitispirillum peregrinum gen. nov., comb. nov.

Abstract: Phylogenetic analysis based on 16S rRNA gene sequences showed that Aquaspirillum itersonii and Aquaspirillum peregrinum form distinct phylogenetic lineages within the Alphaproteobacteria, whereas Aquaspirillum serpens, the type species of the genus Aquaspirillum, belongs to the Betaproteobacteria. A. itersonii and A. peregrinum exhibited 16S rRNA gene sequence similarity values of 82.0–82.4 % to the type strain of A. serpens and of 91.8–92.0 % to each ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 25 publications
1
7
0
2
Order By: Relevance
“…We showed that genera Vallitalea, Christensenella and Insolitispirillum were all enriched in the HUA and the HMT group with high uric acid content. Coincidentally, these bacteria are also gram-negative (Lakhal et al, 2013;Morotomi, Nagai & Watanabe, 2012;Yoon et al, 2007), and furthermore, the genus Insolitispirillum belongs to the phylum Proteobacteria, indicating that genera Vallitalea, Christensenella and Insolitispirillum may be associated with hyperuricemia. Furthermore, Christensenella is highly heritable, and relates to high serum glucose content (Goodrich et al, 2014;Crusell et al, 2018), consistent with previous report showing high genetic trait of hyperuricemia (Krishnan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that genera Vallitalea, Christensenella and Insolitispirillum were all enriched in the HUA and the HMT group with high uric acid content. Coincidentally, these bacteria are also gram-negative (Lakhal et al, 2013;Morotomi, Nagai & Watanabe, 2012;Yoon et al, 2007), and furthermore, the genus Insolitispirillum belongs to the phylum Proteobacteria, indicating that genera Vallitalea, Christensenella and Insolitispirillum may be associated with hyperuricemia. Furthermore, Christensenella is highly heritable, and relates to high serum glucose content (Goodrich et al, 2014;Crusell et al, 2018), consistent with previous report showing high genetic trait of hyperuricemia (Krishnan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The biochemical characteristics of growth under aerobic conditions as well as in NaCl concentrations up to 3% (w/v) along with the positive catalase activity are consistent with the description of the genus Aquaspirillum (Pot and Gillis, 2005). The urea-hydrolysis reaction was in addition negative as reported by Yoon et al (2007). Two very similar strains could be recognized on the basis of the genetic variation in their 16S-rRNA-encoding DNA sequence.…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, intracellular poly-bhydroxybutyrate is present in most species of this genus (Pot and Gillis, 2005). The morphologic features mentioned above were also observed by Yoon et al (2007) in the reclassification of Aquaspirillum itersonii to N. itersonii. Although the chemical composition of the isolates was not analyzed, we did observe inclusion bodies by transmission electron microscopy within the bacterial cells as cited in that description.…”
Section: Discussionmentioning
confidence: 78%
“…A correlation between iron availability with that of porphyrin and haem contents was initially observed in Corynebacterium diphteriae as early as the 1940s (Pappenheimer, ; Pappenheimer and Hendee, ; Rawlinson and Hale, ). Later, Lascelles published a series of studies in Rhodobacter sphaeroides and Novispirillum itersonii [formerly known as Spirillum itersonii and Aquaspirillum itersonii (Yoon et al ., )] where she showed that iron deficiency induces excretion of precursor porphyrins, resulting in a reduction of haem, cytochrome and bacteriochlorophyll content (Lascelles, ; Clark‐Walker et al ., ; Lascelles and Hatch, ; Lascelles et al ., ).…”
Section: Introductionmentioning
confidence: 99%